Coastal Ecotourism Potential of Sorake Beach, South NiasRegency in North Sumatra Province - Mendrofa, Feronika; Yoswaty, Dessy; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Sorake Beach is located in South Nias Regency and facing directly to the Indian Ocean which possessed a wealth of natural and diverse appeal had potential for ecotourism development. This study aims to determine the condition and potential of natural resources that can be developed, to analyze and formulate the concept of ecotourism development strategy in Sorake.Suitability tourism index in Sorake was at suitable level (S2 suitability). The results showed the calculation results of the IFE (internal factors) and EFE (external factor) had a value of 2.92 and 2.91 respectively. The internal factors was stronger than external factors. The priority strategy of future development suggested making programs and environmental activities that environmentaly friendly and making tourist zoning plan.Keywords: Strategy Development, Ecotourism, Tourism Suitability Index, IFE and EFE.